Modified rock mass classification system by continuous rating - Şen, Zekai; Sadagah, Bahaaeldin H. (Elsevier BV, 2003)
It is not the purpose of this paper to propose a new rock mass classification system but rather to improve the existing ones by incorporating some simple quantitative interpretations. The geomechanics classification system of naturally fractured rock masses is modified to decrease personal judgement involved in its calculation. Instead of six parameters in the classical rock mass rating (RMR) system, only five basic parameters are considered in the proposed system, which are namely, rock quality designation (RQD) value with the underlying frequency distribution function of intact lengths; uniaxial or point load strength of intact rock material; conditions of the most unfavorable joints; groundwater condition; and joint orientation. Classical lump-rating system is replaced by continuous grading system which leaves no ambiguity for an inexperienced engineer in allocating grades based on quantitative field or laboratory measurements. Finally, necessary charts are presented for obtaining straightforward design values concerning average stand-up time and corresponding unsupported span of excavations in fractured rock mass; cohesion as well as friction angle of the rock mass. The continuous RMR system is very convenient for calculators or in writing computer software. The proposed methodology reduces the scale of subjectivity and leads to a unique rock mass design value.